Climate philanthropy as a catalyst for advancing the renewable energy transition and climate resilience in Africa - Kwanhi, Thandoluhle; Kagande, Albert Tafadzwa; Van den Berg, Amanda; Mago, Stephen; Makuwira, Jonathan (Frontiers in Climate, 2025)
IntroductionAfrica faces the dual challenges of energy poverty and climate change, necessitating urgent solutions to ensure sustainable development. While renewable energy offers a viable alternative to fossil fuels, its adoption is hindered by financial constraints. Philanthropic funding has emerged as a crucial catalyst for accelerating renewable energy transitions and enhancing climate resilience. The main aim of this study was to investigate the role of philanthropic funding in renewable energy to address climate change in Africa.MethodsThis study employed a bibliometric analysis combined with a systematic literature review guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, with relevant peer-reviewed journal articles published between 2014 and 2024 identified and screened using the Scopus database. The Population, Intervention, Comparison, Outcome, and Context (PICOC) framework. The SALSA framework was used to guide Search, Appraisal, Synthesis, and Analysis of the selected literature to ensure a structured and transparent review process.ResultsFindings indicate an increasing focus on climate-smart technologies, low-carbon development, and climate adaptation strategies, with South Africa and Kenya leading research output in Africa, followed by the USA and the UK. Environmental science was the primary subject area, and Nature was the most influential journal, followed by Climate Policy. Four key thematic areas were identified: adaptation and resilience building, low-carbon transition, governance and financial flows, and agriculture and food security. Despite increasing scholarly attention, significant funding gaps persist, particularly in adaptation-focused initiatives and renewable energy infrastructure, while challenges such as inadequate regulatory frameworks and coordination issues continue to hinder effective philanthropic interventions.DiscussionFuture research should examine the socio-economic implications of climate philanthropic funding to maximise impact, assess its effectiveness in different regions, and develop context-specific climate adaptation strategies. Strengthening governance structures, fostering multi-stakeholder collaborations, and aligning philanthropic investments with national climate policies are critical to enhancing the sustainability of renewable energy projects. This study underscores the need for increased philanthropic engagement in Africa’s energy transition to address energy poverty, mitigate climate vulnerabilities and promote long-term resilience, which will all go a long way in addressing SDG 7. It highlights that, once gaps are identified, climate philanthropy can complement public finance and drive inclusive and long-term climate action across vulnerable sectors such as agriculture, energy, and food security.